Cooperative Hybrid Nonorthogonal Multiple Access-Based Mobile-Edge Computing in Cognitive Radio Networks - Wang, Dawei; Zhou, Fuhui; Lin, Wensheng; Ding, Zhiguo; Al-Dhahir, Naofal (IEEE transactions on cognitive communications and networking, 2022)
In order to efficiently compute the primary data and support the secondary quality-of-service (QoS) requirement, we propose a cooperative hybrid non-orthogonal multiple access (NOMA) scheme for mobile edge computing (MEC) assisted cognitive radio networks. In the proposed scheme, the primary computation task is securely offloaded to the secondary base station, and the hybrid NOMA technique is adopted to provide secondary spectrum access and secure the primary offloading simultaneously. The weighted energy consumption minimization problem for both the primary and secondary systems is first studied under the constraints of the primary system's secure outage probability and the secondary system's QoS requirements, and a two-stage algorithm is proposed to derive the optimal power, time slot and computation task allocation. To motivate the secondary system's cooperation, we optimally allocate the transmit power, time slot and computation task, such that the average secondary system's rate is maximized under the primary system's security requirement, and we derive closed-form expressions for the optimal resource allocations. Numerical results demonstrate the performance superiority of the proposed scheme compared with the full-offloading scheme in terms of the energy consumption and the average secondary rate.